Better Students Ask More Questions.
1 Answer | add yours
-3cos(-3x+a) = 0
Divide by -3 => cos(-3x+a) = 0
The cosine function is cancelling out if `-3x+a = +-pi/2`
Solve `-3x+a = +pi/2gt -3x =pi/2 - a =gt x = -pi/6 + a/3`
Solve `-3x+a = -pi/2gt -3x =-pi/2 - a =gt x = pi/6 + a/3`
The solutions of equation depend on the parameter a: `x =a/3 - pi/6; x = pi/6 + a/3`
Posted by sciencesolve on November 30, 2011 at 2:26 AM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.